DRUG PRESCRIPTION PATTERN IN A TERTIARY HEALTH CENTRE IN IMPHAL- A CROSS SECTIONAL STUDY. - N. MEENA; S. RITA; KH. SANIA MONICA; VIKNESWARAN GUNASEELAN; BANDARILIN THANGKHIEW (International Journal of Pharma and Bio Sciences, 2013)
A cross sectional study was carried out on drug prescription pattern in a tertiary health centre in Imphal. Altogether 220 prescriptions were analysed based on the prescribing indicator formulated by the World Health Organisation (WHO) for improvement in rational drug use. Prescribing indicators like average number of drugs per encounter, percentage of drugs prescribed by generic name, percentage of encounter with an antibiotic prescribed, percentage of encounters with an injection prescribed, percentage of drugs prescribed from essential drugs list (EDL) were studied. The present study showed a trend towards irrational prescribing.